2021
DOI: 10.3390/ijerph182312650
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Efficiency Evaluation of China’s Power Industry Based on the Two-Stage Network Slack-Based Measure Model

Abstract: How to achieve the continuous improvement of the environmental performance level of the power industry within the requirements of clean and low-carbon energy development is the fundamental requirement and inevitable choice for the construction of ecological civilization and sustainable development. From the perspective of environmental protection, based on the Data Envelopment Analysis (DEA) method and the internal mechanism of power system production and supply, the power industry environmental efficiency eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…To make a thorough inquiry of the regional disparities in power efficiency, we divide China into six major regional power networks based on the classification standards of regional power networks, i.e., Northeast, North China, Central China, East China, South China, and Northwest. The regional efficiency level of MTE and ETE from high to low is East (Central) China, Central (East) China, South China, North China, Northeast and Northwest, and the conclusion has been confirmed by other studies [38]. It shows that the ranking of MTE hardly changes after the inclusion of environment constraints, as shown in Table 3 and Figure 2.…”
Section: Technical Efficiency In Power Industrysupporting
confidence: 64%
“…To make a thorough inquiry of the regional disparities in power efficiency, we divide China into six major regional power networks based on the classification standards of regional power networks, i.e., Northeast, North China, Central China, East China, South China, and Northwest. The regional efficiency level of MTE and ETE from high to low is East (Central) China, Central (East) China, South China, North China, Northeast and Northwest, and the conclusion has been confirmed by other studies [38]. It shows that the ranking of MTE hardly changes after the inclusion of environment constraints, as shown in Table 3 and Figure 2.…”
Section: Technical Efficiency In Power Industrysupporting
confidence: 64%
“…In an empirical study of the environmental performance of urban agglomerations in the Beijing-Tianjin-Hebei region from 2003 to 2015, Xue et al found fluctuating changes in performance differences between regions but a trend in expansion in the last two years [31]. Moreover, a study of the power industry's environmental efficiency showed no significant contraction trend between regions [32]. In contrast, Wang and Wang examined the environmental regulation and tourism eco-efficiency of urban agglomerations in the Yangtze River Delta region using the entropy power method and the super-efficiency slacks-based measure (SBM) model.…”
Section: Disparities In Environmental Regulation Performancementioning
confidence: 99%
“…In addition to analysing the efficiency of energy consumption, the doctrine also analyses the efficiency levels of distribution channels. Using the DEA model, Wei et al (2021) sought to estimate the efficiency levels in energy production, transmission, and distribution of 30 municipalities in China between 1998 and 2019. The study concludes that average efficiency is low and the disparities between municipalities are considerable.…”
Section: Introductionmentioning
confidence: 99%